T-Cell Large Granular Lymphocytic Leukemia with Extremely Rare Immunophenotype (CD4/CD8 Double-Positive) Followed by Multiple Myeloma Diagnosis - Dina Soliman; Sherin Sallam; Susanna Akiki; Deena Mudawi; Feryal Ibrahim (Case Reports in Hematology)
T-cell large granular lymphocytic leukemia is characterized by clonal expansion of a CD3+/CD57+ subpopulation, which are typically CD8+ positive cytotoxic T- cells, and can only be diagnosed if there is a persistent, greater than 6 months, elevation of LGL in the blood (usually 2–20 × 109/L), in the absence of an identifiable cause. T-LGLL has been associated with reactive conditions such as autoimmune diseases and viral infections and has also been reported in association with hematologic and non-hematologic malignancies. We report a case of asymptomatic CD4/CD8 double-positive T-LGLL. Flow cytometry on peripheral blood revealed a subpopulation of CD4/CD8 double-positive T cells expressing CD57 and cTIA. Clonality was established by flow cytometric analysis of T-cell receptor V(â) region repertoire which showed that >70% of the cells failed to express any of the tested V(â) regions. Clonality was further confirmed by PCR with the detection of clonal TCR beta and TCR gamma gene rearrangements. Six months later, she presented with persistent lower back pain and diagnosed with IgG kappa multiple myeloma. CD4/CD8 double-positive T-large granular leukemia is the first case reported in the literature. This rare phenotype is either underreported or a truly rare clinical entity. More studies are warranted to characterize the pathogenesis and clinical characteristics of this group of patients and to further assess the relationship between multiple myeloma and T-LGLL as a cause-and-effect relationship or simply related to the time at which diagnosis has been made.